The effect of non-polar solvent extraction of Piper Ribesioides (Sireh Hutan) on Candida Albicans Morphology - P.M, Ridzuan; S.V, Sathiya; Draman, Samsul; Maizatu-Syamemy, M.N.; Masharudin, A.W.; Amilin, A.N.; Farihah, S.N.; Badhrulhisham, Aisyah; Naimat, Faiza (Universiti Kuala Lumpur, 2021)
Introduction: Piper ribesioides is a vigorous climber, found in Indonesia and the Peninsular Malaysia, the root of this piper is used to treat an illness caused from asthma, diarrhoea and abdominal pain. Stems of P. ribesioides have long been used to flavour food giving its spicy and peppery taste. Candida albicans is a commensal life form in the human cutaneous and mucosal verdure, however can turn into a noteworthy human contagious pathogen given the best possible conditions considering hyphal separation, biofilm arrangement, and excess. This fungus is also responsible in causing sexually transmitted infection. The most basic regions for candidiasis are the oral and gastrointestinal tract, the vaginal and the skin. The aim of this study is to identify the potential activities of non-polar extraction of P. ribesiodes on C. albicans morphology. Methods: P. ribesiodes was extracted using n-hexane solvent and serial dilution method was used to produce concentration from 500, 250, 125, 62.5, 31.3, 15.63, 7.81, 3.91, 1.96 and 0.98 mg/ml. Sensitivity test of C. albicans was measured through the diameter of inhibition zone when treated with P. ribesiodes. Minimum Inhibitory Concentration (MIC) and Minimum Fungicidal Concentrations (MFC) were determined by using broth micro-diluted method. Morphology study was done by using Scanning Electron Microscope (SEM). Results: The largest zone of inhibition in 24 hours was at 500 mg/ml concentration. The diameter was nearly 10.333 ± 2.309 mm. The Minimum Inhibitory Concentration and Minimum Fungal Concentration were 15.63 mg/ml and 31.25 mg/ml respectively. Morphology study revealed erosion and damage of cell wall of C. albicans. Conclusion: Morphology of C. albicans were altered when treated with n-hexane extraction of P. ribesiodes.